2021
DOI: 10.13045/jar.2021.00171
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Korean Medicine Treatment for Postherpetic Neuralgia

Abstract: The purpose of this study was to analyze the Korean medicine treatment methods for Postherpetic Neuralgia (PHN) in Korea. There were 5 online databases searched (OASIS, NDSL, RISS, KISS and KMBASE) for studies which were related to PHN. A total of 12 studies were selected. Various treatments such as acupuncture, herbal medicine, and moxibustion were reported treatments for PHN, some of which included Western medicine and Korean medicine treatment. Korean herbal medicine was the most frequently used treatment m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…[7] Traditional medicines, such as acupuncture, moxibustion, and herbal medicine, can be considered potential treatments for PHN. According to a review of traditional medicine for PHN, [12] acupuncture and herbal medicine are most commonly used clinically to relieve pain and improve comorbidities. Although many systematic reviews [13][14][15] have shown that acupuncture is effective for patients with PHN, there are few reviews on the effectiveness of herbal medicine for patients with PHN.…”
Section: This Study Was Supported By the Korea Institute Of Oriental ...mentioning
confidence: 99%
“…[7] Traditional medicines, such as acupuncture, moxibustion, and herbal medicine, can be considered potential treatments for PHN. According to a review of traditional medicine for PHN, [12] acupuncture and herbal medicine are most commonly used clinically to relieve pain and improve comorbidities. Although many systematic reviews [13][14][15] have shown that acupuncture is effective for patients with PHN, there are few reviews on the effectiveness of herbal medicine for patients with PHN.…”
Section: This Study Was Supported By the Korea Institute Of Oriental ...mentioning
confidence: 99%
“…Since chronic pain diseases are accompanied by various symptoms as well as the pain itself, in Korea, these treatments are mainly used clinically in the form of integrative Korean medicine treatment (KMT) by combining these treatments. Integrative KMT, especially, is frequently used in clinical practice to treat the complex symptoms of PHN [32]. Many clinical studies are confined to nociceptive pain, but there is still a lack of evidence regarding neuropathic pain [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…2 Herbal medicine treatment has been used to treat a range of pain-related conditions, and several reviews have demonstrated that herbal medicine can be an effective treatment for patients with PHN. [5][6][7] Qua et al have found that herbal medicine groups significantly alleviated pain intensity compared to western medicine groups, 5 and Liang et al further have shown that herbal medicine as an add-on therapy to pharmacotherapy had a better effect in reducing pain intensity and depression symptom severity compared to pharmacotherapy alone. 6 Paeoniae Radix and Glycyrrhizae Radix, which are the main herbs of Sogeonjungtang (SGJT), have already been used as a sedative, pain reliever, and anti-spasmodic in East Asia through anticholinergic, prostaglandin-productioninhibiting, antioxidation, and anti-inflammation as Jakyakgamchotang (also known as Shakuyakukanzo-to, Shaoyaogancao-tang).…”
Section: Introductionmentioning
confidence: 99%